The Influence of Adding Fixative Compounds to Essential Oils as Repellents - Fidela Hafiz Rudiana; Gita Cahya Eka Darma (UNISBA Press, 2023)
Abstract. Mosquitoes have long been recognized as disease vectors in Indonesia. Through their bites, mosquitoes can transmit disease-causing viruses to humans as hosts. Essential oils, also known as volatile oils, ethereal oils, or essential oils, contain compounds that are either volatile or non-volatile. Repellents are chemical substances used to avoid insect bites and disturbances, applied topically or as a spray. This research aims to explore the potential of essential oils as repellents to reduce the side effects of chemical mosquito repellents and to examine the influence of fixative compounds in enhancing mosquito bite protection. The research method employed is a Systematic Literature Review (SLR), which involves gathering various studies' data regarding the impact of combining fixative compounds with essential oils on mosquito repellency. The results of the literature review demonstrate the potential of essential oils as active compounds for use in repellents and indicate the effect of adding fixative compounds to essential oils in repellent formulations. Abstrak. Nyamuk telah lama dikenal sebagai vektor penyakit di Indonesia. Melalui gigitannya nyamuk dapat menyebarkan virus penyakit kepada manusia sebagai host. Minyak atsiri adalah minyak yang juga dikenal dengan essential oil, ethereal oil, atau volatile oil. Minyak atsiri mengandung senyawa yang mudah menguap (volatile) atau bahan yang tidak mudah menguap (non-volatile). Repellent adalah suatu bahan kimia yang digunakan dengan tujuan untuk dapat menghindari gigitan serta gangguan serangga, baik dengan cara dioleskan maupun disemprot. Penelitian dilakukan bertujuan untuk dapat melihat potensi minyak atsiri sebagai repellent supaya dapat menekan efek samping penggunaan obat nyamuk kimia, serta untuk melihat pengaruh penggunaan fiksatif dalam meningkatkan daya proteksi gigitan nyamuk. Metode yang dilakukan dalam penelitian adalah Systematic Literature Review (SLR) dengan mengumpulkan berbagai data penelitian mengenai pengaruh kombinasi fiksatif dengan minyak atsiri terhadap daya tolak nyamuk. Hasil studi pustaka menunjukkan adanya potensi minyak atsiri sebagai senyawa aktif yang dapat digunakan sebagai repellent dan terdapat pengaruh penambahan fiksatif pada minyak atsiri dalam sediaan repellent.